Factor Structure and Other Psychometric Properties of the Social Phobia Inventory in Korean Samples. (2nd October 2018) - Cho, Yongrae; Choi, Younghee; Kim, Sunyoung; Hong, Sehee
ABSTRACT: We examined the factor structure and other psychometric properties of the Social Phobia Inventory (SPIN) in Korean nonclinical ( N 1 = 457, N 2 = 444) and clinical undergraduate samples ( N 3 = 12). Results support the revised 3-factor structure and applicability of the SPIN as a measure yielding valid and reliable scores of social anxiety to Koreans.